Controlling pore structure and conductivity in graphene nanosheet films through partial thermal exfoliation. (15th April 2021) - Kwon, Yongbeom; Liu, Muchun; Castilho, Cintia; Saleeba, Zachary; Hurt, Robert; Külaots, Indrek
Abstract: Thermal exfoliation is an efficient and scalable method for the production of graphene nanosheets or nanoplatelets, which are typically re-assembled or blended to form new macroscopic "graphene-based materials". Thermal exfoliation can be applied to these macroscopic graphene-based materials after casting to create internal porosity, but this process variant has not been widely studied, and can easily lead to destruction of the physical form of the original cast body. Here we explore how the partial thermal exfoliation of graphene oxide (GO) multilayer nanosheet films can be used to control pore structure and electrical conductivity of planar, textured, and confined GO films. The GO films are shown to exfoliate explosively when the instrument-set heating rates are 100 K/min and above leading to complete destruction of the film geometry. Textured films with engineered micro-wrinkling and crumpling show similar thermal behavior to planar films. Here, we also demonstrate a novel method to produce fairly large size intact rGO films of high electrical conductivity and microporosity based on confinement. Sandwiching GO precursor films between inert plates during partial exfoliation at 250 °C produces high conductivity and porosity material in the form of a flexible film that preserves the macroscopic structure of the original cast body. Graphical abstract: Image 1 Highlights: GO film partial thermal exfoliation allows to control rGO film pore structure and electrical conductivity. Textured films with engineered micro-wrinkling and crumpling show similar thermal exfoliation behavior to planar films. Planar and textured GO films exfoliate explosively when instrument heating rates are 100 K/min and above. GO film confinement prior to thermal exfoliation allows to produce electrically conductive and semi-porous rGO films.